Optimizing Acidic Reductive Leaching for Lithium Recovery: Enhancing Sustainable Lithium Supply for Energy Markets - Agnieszka Sobianowska-Turek; Amelia Zielińska; Weronika Urbańska; Anna Mielniczek; Agnieszka Fornalczyk; Szymon Pawlak; Tomasz Małysa; Janusz Cebulski (Energies)
The growing demand for lithium, driven by its crucial role in energy storage technologies such as lithium-ion batteries for electric vehicles, renewable energy storage, and portable electronics, is intensifying the need for sustainable extraction methods. While lithium is sourced from both primary and secondary resources, particularly from recycled materials, the recovery from spent lithium-ion batteries remains challenging. This article presents acidic reductive leaching as a promising alternative for lithium extraction from secondary sources and unconventional ores, emphasizing its potential benefits, such as higher recovery rates, faster processing, and adaptability to various waste materials. Notably, this method facilitates the selective recovery of lithium before cobalt and nickel, providing a strategic advantage. This study highlights the lack of optimization studies on leaching conditions (e.g., acid concentration, reducing agents, temperature, and time) that could maximize lithium recovery while minimizing environmental and economic costs. The article aims to investigate and optimize the parameters of acidic reductive leaching for more efficient lithium recovery. Additionally, the results contribute to the principles of the circular economy and sustainable supply chains in the energy sector, providing a method to reduce dependency on geopolitically constrained lithium resources and supporting the global energy transition toward cleaner energy solutions.